DAMPAK PENERAPAN MODEL PEMBELAJARAN PROBLEM SOLVING ATAS PENINGKATAN KEMAMPUAN MEMECAHKAN MASALAH SISWA DALAM MATA PELAJARAN PAI DI SEKOLAH MENENGAH ATAS - Rosfiani, Okta; Hendrayani, Dini; Santoso, Nisrina Azizah; Yaqutah, Akmal; Ramadhan, Rizky; Firdaus, Kesha Irsyad (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2025)
The problem-solving learning model requires students to analyse issues, formulate alternative solutions, and evaluate their results. In the context of Islamic Religious Education, the application of problem-solving is expected to help students relate religious teachings to life issues more practically. This study aims to analyse the impact of the application of the problem-solving learning model on improving students' problem-solving abilities in Islamic Religious Education (PAI) subjects in senior high schools. The research method uses a qualitative approach with data collection techniques through observation, in-depth interviews, and document analysis. The research subjects involved Islamic Religious Education teachers and students in three high schools that have implemented this model. The results of the study indicate that the problem-solving model is effective in improving students' analytical abilities in identifying religious problems, connecting them to Islamic sources (the Qur'an, Hadith, and opinions of scholars), and formulating relevant solutions. In addition, this model encourages active student participation and collaboration in discussions. However, its implementation faces obstacles such as limited time for teachers to prepare contextual materials and variations in students' religious understanding. This study recommends teacher training for the development of case studies, integration with other subjects, and the use of supporting technology. These findings provide important contributions to the development of Islamic Religious Education learning strategies based on problem solving. ABSTRAKModel Pembelajaran Problem Solving mengharuskan siswa untuk menganalisis isu, merumuskan alternatif untuk solusi, dan menilai hasilnya. Dalam konteks PAI, penerapan Problem Solving diharapkan dapat membantu siswa mengaitkan ajaran agama dengan isu kehidupan secara lebih praktis. Penelitian ini bertujuan untuk menganalisis dampak penerapan model pembelajaran problem solving terhadap peningkatan kemampuan memecahkan masalah siswa dalam mata pelajaran Pendidikan Agama Islam (PAI) di Sekolah Menengah Atas. Metode penelitian menggunakan pendekatan kualitatif dengan teknik pengumpulan data melalui observasi, wawancara mendalam, dan analisis dokumen. Subjek penelitian melibatkan guru PAI dan siswa di tiga SMK yang telah menerapkan model ini. Hasil penelitian menunjukkan bahwa model problem solving efektif dalam meningkatkan kemampuan analitis siswa dalam mengidentifikasi masalah keagamaan, menghubungkannya dengan sumber Islam (Al-Qur’an, Hadis, dan pendapat ulama), serta merumuskan solusi yang relevan. Selain itu, model ini mendorong partisipasi aktif siswa dan kolaborasi dalam diskusi. Namun, implementasinya menghadapi kendala seperti keterbatasan waktu guru dalam menyiapkan materi kontekstual dan variasi pemahaman keagamaan siswa. Penelitian ini merekomendasikan pelatihan guru untuk pengembangan studi kasus, integrasi dengan mata pelajaran lain, serta pemanfaatan teknologi pendukung. Temuan ini memberikan kontribusi penting dalam pengembangan strategi pembelajaran PAI yang berbasis pemecahan masalah.